Akulturasi Islam dan Budaya Lokal - Bakri , Wahyuddin (Program Pascasarjana, UIN Alauddin Makassar, 2024)
Cultural differentiation is a necessity in the interaction of life, from various cultural identities and social backgrounds that surround it. Intensely this phenomenon can be observed in the lives of residents of Islamic boarding schools. The pattern of interaction between student, teacher and community around the boarsing school is basically culturally conditioned. Type of research used is empirical qualitative, the approach method used is sociological culture, which studies social interactions with all aspects related to these interactions. The results of the study show an overview of the process of cultural acculturation in the Darul Istiqamah Islamic boarding school. The interaction between the students Darul Istiqamah Islamic Boarding School is actually a musical experience, because at first they come from different socio-cultural backgrounds. logistics of the interaction and activity of the students to establish social relationships that allow this acculturation process to take place. Cultural acculturation in the life of Darul Istiqamah Islamic boarding school students is manifested through multicultural interaction practices. The next process, the students who are ethnically different then interact with each other in the cultural setting of the pesantren to form their own community or subculture in the midst of the cultural diversity of the community. Abstrak Perbedaan budaya adalah keniscayaan dalam interaksi kehidupan masyarakat, keberagaman identitas kebudayaan serta latar masyarakat yang melingkupinya. Fenomena ini diamati dalam kehidupan sosial pondok pesantren Darul Istiqamah. Interaksi sosial warga pondok pesantren dan masyarakat di sekitar pada dasarnya terkondisikan secara kultural. Dalam hal ini jenis penelitian adalah kualitatif empirik, dengan metode pendekatan yaitu sosiologi kebudayaan, yang mempelajari tentang relasi sosial dengan segala aspek. Hasil penelitian memberi gambaran tentang proses akulturasi budaya di lingkungan pesantren Darul Istiqamah. Interaksi sosial di antara santri dan masyarakat sekitar, sesungguhnya merupakan suatu pengalaman peralihan, dikarenakan pada awalnya warga pesantren berasal dari latar belakang budaya yang berbeda-beda sehingga terjadi interaksi maupun keaktifan para santri untuk menjalin hubungan sosial memungkinkan proses akulturasi ini berlangsung, akulturasi ini terwujud melalui praktik-praktik interaksi multikultural, pada proses selanjutnya warga pondok pesantren yang berbeda secara kultur kemudian berinteraksi satu sama lainnya dalam setting kultur pesantren hingga membentuk komunitas atau subkultur tersendiri di tengah keragaman budaya masyarakat.